Przeobrażenia demograficzne w parafii Nowe Kramsko w latach 1707-1806 w świetle "Ksiąg ochrzczonych i zmarłych" = Demographic transformations in the parish of Nowe Kramsko in the years 1707-1806 in the light of the "Register of the baptized and the dead" - Benyskiewicz, Krzysztof (1959- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article entitled is an analysis of the changes taking place in rural communities over the centuries. The basis of the study are the registers of the baptized and the dead kept in the parish consisting of three villages: Nowe Kramsko, Stare Kramsko i Wojnowo. The parish registers were founded there in the early seventeenth century. The records were made by the monks of the Cistercian monastery in Obra. Thanks to the registers we see more views of a long process re-population of the demographic crisis associated with the activities of the Great Northern War.
Keywords: Nowe Kramsko (pow. babimojski); demografia; księgi ochrzczonych i zmarłych; demography; the books on baptised and dead